The Implications of Islamic Behavior on Commitment and Performance by Employees - Pratami, Eggi Indriani; Juniarti, Atty Tri; Setia, Bayu Indra (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2023)
A factor that encourages commitment is the need for Islamic principles and values to be practiced in Islamic organizations. The purpose of this study is to evaluate the extent to which Islamic conduct influences commitment and the implications for employee performance. This study's sample size was 282 employees. Path analysis and hypothesis testing are used for data analysis. According to the study's findings, the path coefficient of Islamic conduct toward commitment is 0.438, a positive value affecting commitment, with a coefficient of determination or R2 value of 0.192 or 19.2%. The commitment to performance path coefficient is 0.638, which is a positive value affecting performance, with a determination coefficient or R2 value of 0.407, or 40.7%. Islamic conduct has a 0.279 indirect impact on performance through dedication. This study concludes that practicing Islam has a favorable and significant impact on commitment. Employee performance is positively and significantly impacted by commitment.